2017
DOI: 10.3389/fimmu.2017.00524
|View full text |Cite
|
Sign up to set email alerts
|

HPV16-E7-Specific Activated CD8 T Cells in E7 Transgenic Skin and Skin Grafts

Abstract: Human papillomavirus (HPV) 16 E7 (E7) protein expression in skin promotes epithelial hyperproliferation and transformation to malignancy. Grafts of murine skin expressing E7 protein as a transgene in keratinocytes are not rejected from immunocompetent recipients, whereas grafts expressing ovalbumin (OVA), with or without coexpression of E7 protein, are promptly rejected, demonstrating that E7-associated non-antigen-specific local immunosuppression is not a major determinant of lack of rejection of E7 transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…We hypothesise that these factors, when present in the K14E7 skin environment, co-ordinately induce ineffective CD8 effector T cell responses against K14E7 skin grafts. More recently, the overarching hypothesis has been refined in that E7-induced hyperplasia rather than expression of E7, is responsible for the recruitment, programming and/or retention of these immunosuppressive cells and molecules in the K14E7 hyperplastic epithelium milieu, as mice expressing E7 protein from the Keratin 14 promoter, and with a mutated retinoblastoma protein that is functionally effective but cannot bind E7, have no hyperplasia and no inflammatory infiltrates [20] , [31] , [89] . Hyperplastic murine K14E7 transgenic skin thus models some important aspects of the cellular infiltrate and immunosuppressive cytokine secretion profile in cervical cancer and high-grade CIN lesions in human patients.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesise that these factors, when present in the K14E7 skin environment, co-ordinately induce ineffective CD8 effector T cell responses against K14E7 skin grafts. More recently, the overarching hypothesis has been refined in that E7-induced hyperplasia rather than expression of E7, is responsible for the recruitment, programming and/or retention of these immunosuppressive cells and molecules in the K14E7 hyperplastic epithelium milieu, as mice expressing E7 protein from the Keratin 14 promoter, and with a mutated retinoblastoma protein that is functionally effective but cannot bind E7, have no hyperplasia and no inflammatory infiltrates [20] , [31] , [89] . Hyperplastic murine K14E7 transgenic skin thus models some important aspects of the cellular infiltrate and immunosuppressive cytokine secretion profile in cervical cancer and high-grade CIN lesions in human patients.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have demonstrated that activated antigen-specific CD8 T cells can enter both hyperplastic (K14.E7) and normoplastic (K14.E7xRb ΔL/ΔL ) E7-expressing epidermis but only a very low number of antigen-specific T cells are retained in the K14.E7xRb ΔL/ΔL epidermis (20). Graft rejection requires effector T cells to engage antigen expressing keratinocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular binding of E7 to the retinoblastoma (Rb) protein leads to a dysregulated cell cycle within keratinocytes and the subsequent development of a precancerous, hyperplastic epithelium resembling actinic keratosis, a precursor lesion which can progress to squamous cell carcinoma in human patients ( 143 ). One feature of the E7-driven hyperplasia is a chronic inflammatory/wound healing microenvironment associated with elevated levels of IFN-γ and immune cell infiltration ( 144 , 145 ). Chronic IFN-γ production in the skin, from cells such as infiltrating NKT cells, results in an immunosuppressed microenvironment via mediators such as IDO ( 146 148 ).…”
Section: Introductionmentioning
confidence: 99%